Activating RuOCo Interaction on the a‐Co(OH)2@Ru Interface for Accelerating the Volmer Step of Alkaline Hydrogen Evolution. Issue 2 (5th January 2023) - Zhao, Jun; Wang, Jiajun; Zheng, Xuerong; Wang, Haozhi; Zhang, Jinfeng; Ding, Jia; Han, Xiaopeng; Deng, Yida; Hu, Wenbin
Abstract: The state‐of‐the‐art active hydrogen evolution reaction (HER) catalysts in acid electrolytes generally lose considerable catalytic performance in alkaline electrolytes mainly due to the additional water dissociation step. Designing composite materials is an effective strategy to accelerate alkaline water electrolysis by optimizing the electronic structure of materials. Here, different phases of Co(OH)2 ‐supported Ru clusters (α/β‐Co(OH)2 @Ru) are prepared for enabling a highly efficient electrocatalytic HER performance in alkaline solution. The prepared α‐Co(OH)2 nanosheets facilitate the loading of uniform and high‐density Ru clusters and the formed highly active RuOCo bonds at the interface. The synergistic interaction endows the hybrid catalyst with low overpotential of 33 mV at 10 mA cm −2 . Moreover, the homemade anion exchange membrane water electrolysis cell based on α‐Co(OH)2 @Ru affords a cell voltage of 2 V to drive a current density of 270 mA cm −2 and performs stably during continuous operation for over 100 h. Density functional theory calculations demonstrate that active RuOCo bonds in α‐Co(OH)2 @Ru optimize the energy barriers for H2 O dissociation and OH − desorption to facilitate the Volmer reaction step. This work offers a strategy for designing interfacial chemical bonds for high electrocatalytic activity. Abstract : The Ru clusters supported on different phases of Co(OH)2 are prepared by a two‐step strategy of coprecipitation and impregnation methods. This effectively regulates the interfacial interactions and the electronic environment of the hybrid catalysts, reducing energy barriers for H2 O dissociation and OH − desorption, and greatly promoting the kinetics of alkaline hydrogen evolution reaction.